Study Of The Prevalence Of Gastrointestinal Tract Lymphoma Accourding To Histology Type And Comparing The Effects Of Treatement On Each Type Of Patients At Al-Bayrouni University Hospital - ديوب, آصف (Latakia University Journal -Medical Sciences Series, 2021)
background: The GI system is the most common external site involving lymphomas, with the majority being non-Hodgkin's. Although lymphoma can involve any part of the GI tract, the most common sites in the order in which it occurs are the stomach followed by the small intestine. Typically, gastrointestinal lymphoma is secondary to node injury, and primary gastrointestinal lymphomas are relatively rare. Diffuse large B cell lymphoma is the most common pathological type of gastrointestinal lymphoma, although the frequency of other forms has increased recently in certain regions of the world. There has been a huge leap in the diagnosis, regulation and management of gastrointestinal lymphoma in the past two decades, attributed to better insight into its etiology and molecular aspects as well as knowledge about its critical signaling pathways. The aim of this study: This study aims to investigate the anatomical, histological, and clinical distribution ratios in patients with gastrointestinal lymphoma, and to compare the results of conservative treatment and surgical treatment or the combination of them for each histological pattern. Methods: cross-sectional Observational retrospective study from. The endoscopic lesions are described and their location is determined, then a microscopic examination is performed on biopsies taken from the affected part of the digestive tract, immunostaining and upper and lower gastrointestinal endoscopy is performed. Surgical, radial, or joint Results: 62 patients with gastrointestinal lymphoma, including 58% male and 42% female, participated in the study. The injuries were distributed according to the histological type (histopathology) as follows: Low grade MALT Lymphoma (61.3%) - High Grade DLBCL (25.8%) - Burkitt's Lymphoma (4.8%) Mantle Lymphoma (3.2%) - Lymphoblastic Lymphoma (3.2%) - Peripheral T-Cell Lymphoma (EATL) (1.6%) The cases of infection in the digestive tract (the affected part of the digestive tube) were distributed according to the following: the stomach (91.3%), the small intestine (6.1%), the colon (1.7%), the rectum (0.9%), and the results of the treatments are shown according to each Histological pattern during the study Conclusion: Conducting endoscopic investigations in patients with gastrointestinal complaints is very important in early detection of infection to achieve greater rates of recovery and relentlessness.